Factors associated with unmet healthcare needs in patients using Primary Care Access Points for unattached patients in Quebec (Canada) - Mylaine Breton; Catherine Lamoureux-Lamarche; Véronique Deslauriers; Djamal Berbiche; Maude Laberge; Annie Talbot; Aude Motulsky; Marie-Pascale Pomey; Isabelle Gaboury (PLoS ONE, 2026)
Background Access to primary care is an important component of health systems. Given the barriers experienced by unattached patients to accessing primary care in Quebec (Canada), the Ministry of Health mandated the province-wide implementation of Primary care access points for unattached patients ( Guichet d’accès première ligne ; GAP), an organizational innovation designed to orient patients to the most appropriate professional or service. This study aims to 1) document the factors associated with unmet healthcare needs after receiving GAP services and 2) assess whether those factors vary by GAP orientation. Methods This cross-sectional study builds on data collected between April and July 2024 using an online patient questionnaire. All patients with a valid email address registered on the centralized waiting list for unattached patients in three local health territories (LHTs) received an email invitation to participate in the survey. The total sample included 20,282 participants who responded to the questionnaire and used the GAP. Results The findings showed that younger age, self-reporting poor/fair physical and mental health, receiving services in LHT 3 and reporting an emergency room visit were associated with increased likelihood of reporting unmet needs. Stratified analyses suggested that some characteristics (age, use of emergency room) were associated with unmet needs across orientations, while others (self-reported physical and mental health) were associated with specific orientations. Conclusion This study serves as a first step in deepening our understanding from a patient perspective of how to better plan primary care services and improve unattached patients’ experiences using the GAP. The findings showed that patients oriented to other professionals than a medical appointment with a family physician had the highest percentage of unmet needs. The next step involves an in-depth exploration of the reasons for patients’ unmet needs, enabling the development of more precise and effective strategies to address them.